PENGARUH E-WOM DAN BRAND IMAGE INSTAGRAM TMII JAKARTA TERHADAP KEPUTUSAN BERKUNJUNG - Malia Sudarno Putri, Del; Mahadewi, NPE.; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024)DO - 10.24843/IPTA.2024.v12.i02.p02, 2025)
Nowadays, with the rapid development of technology, everyone has the ability to access the internet quickly, especially when planning a tour. Through brand image information uploaded via social media, there will be electronic word of mouth (e-wom) which makes it easier for prospective tourists to determine their tour. This study aims to determine the effect of electronic word of mouth and brand image on the decision to visit domestic tourists to Taman Mini Indonesia Indah. In this study, to determine the sample using purposive sampling method with a sample of 100 respondents. In this study, data collection techniques using observation, interviews, questionnaires, documentation and literature studies. The data analysis used is descriptive quantitative with multiple linear regression analysis with the help of SPSS software version 25.0. The results of this study indicate that: (1) electronic word of mouth has a positive and significant effect on the decision to visit domestic tourists to Taman Mini Indonesia Indah. (2) Brand Image also has a positive and significant effect on the decision to visit domestic tourists to Taman Mini Indonesia Indah. (3) electronic word of mouth and brand image influence the decision to visit Indonesian tourists to Taman Mini Indonesia Indah.